2022
DOI: 10.15408/sjie.v11i2.26145
|View full text |Cite
|
Sign up to set email alerts
|

Does Economic Growth Mediate Investment, Inflation, and Human Development Investment on Poverty in Indonesia?

Abstract: Poverty is a classic yet interesting topic of discussion because the problem of poverty has not been solved. This study analyzed the role of economic growth in mediating the effects of investment, inflation, and Human Development Investment (HDI) on poverty in Indonesia. Using the multiple regression method of path analysis and the data from 32 provinces in Indonesia, the results showed that investment had a positive effect on economic growth and poverty, but inflation had no effect on economic growth and pove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…An increase in HDI increases labor productivity and therefore the ability of the community due to improved capabilities of community and individuals. These findings are consistent with the previous research by (Fitriady et al, 2022;Rohmi et al, 2021), which also found a negative association between HDI and poverty. The components of HDI are directly linked to community productivity.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…An increase in HDI increases labor productivity and therefore the ability of the community due to improved capabilities of community and individuals. These findings are consistent with the previous research by (Fitriady et al, 2022;Rohmi et al, 2021), which also found a negative association between HDI and poverty. The components of HDI are directly linked to community productivity.…”
Section: Resultssupporting
confidence: 93%
“…Improving living standards, health, and education can be crucial strategies for breaking the cycle of poverty. Previous research has shown that poverty reduction can be achieved through improving the standard of human resources including health, education, and living standards as measured by HDI (Fitriady et al, 2022;Nainggolan, Sembiring, & Nainggolan, 2021;Purnomo, 2019). However, according to research by (Ipmawan et al, 2022), poverty is not significantly affected by HDI, and therefore an increase in HDI is not invariably accompanied by a decline in poverty.…”
Section: Introductionmentioning
confidence: 99%